Clinical efficacy of Fufang Yinhua Jiedu (FFYH) granules in mild COVID-19 and its anti-SARS-CoV-2 mechanism by blocking autophagy through inhibiting the AKT/mTOR signaling pathway - Wang, Wenlei; Zheng, Zhihui; Qi, Xiaoyuan; Wei, Hailin; Mao, Xuhua; Su, Qin; Chen, Xiang; Feng, Yan; Qiao, Guohong; Ma, Tieliang; Tang, Zhian; Zhou, Guangming; et al. (Frontiers in Pharmacology, 2024)
Background: Fufang Yinhua Jiedu granules (FFYHs) are recommended for treating coronavirus pneumonia in China. However, its anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) activity and clinical efficacy against COVID-19 remain to be confirmed.Aims: Our study aimed to investigate the anti-SARS-CoV-2 effect and potential mechanism of FFYH.The activity of FFYH against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was evaluated via cell pathogenic effects, immunoblotting, immunofluorescence staining and qRT-PCR. The potential mechanism of FFYH against SARS-CoV-2 was investigated by immunoblotting. One head-to-head randomized controlled trial was designed to evaluate the clinical efficacy of FFYH in mild COVID-19. Two hundred patients were randomly recruited to receive either FFYH or LHQW (Lianhua Qingwen granules). Results: The in vitro results indicated that FFYH effectively inhibited SARS-CoV-2 replication by suppressing CPE and decreasing viral RNA and protein expression. A time-of-drug-addition assay confirmed that FFYH mainly targeted the binding and replication stages of the SARS-CoV-2 life cycle. Mechanistic studies revealed that blocking SARS-CoV-2-triggered autophagy may be the primary mechanism by which FFYH protects against SARS-CoV-2 infection by regulating the phosphatidylinositol 3-kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR) signaling pathway. Clinical results confirmed that FFYH effectively shortened the recovery time of clinical symptoms and viral nucleic acid negativity, improved abnormal hematology parameters and controlled excessive cytokine responses in mild COVID-19 patients. Subgroup analysis revealed that FFYH improved the recovery time of clinical symptoms, improved hematological parameters and controlled excessive cytokine storms to a greater extent in the mild COVID-19 male subgroup, abnormal hematology subgroup and 32-42-year-old subgroup than in the corresponding LHQW subgroup (P<0.05). No patients progressed to severe or critical cases. Conclusion: Our results indicate that FFYH not only has good antiviral activity against SARS-CoV-2 but also has significant efficacy against COVID-19, indicating that FFYH may be a novel complementary option for treating COVID-19.